1989
DOI: 10.1055/s-2007-1012966
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Right Versus Left Hepatic Duct Endoprosthesis Insertion in Malignant Hilar Biliary Obstruction

Abstract: Endoscopic endoprosthesis insertion plays an increasingly important role in the palliation of jaundice in patients with unresectable malignant hilar biliary obstruction (HBO). Drainage of both obstructed lobes in Types II and III HBO is not necessary to achieve adequate palliation, providing 25% of the liver volume is drained by a single endoprosthesis. The anatomy of the main hepatic ducts suggests some benefit may accrue from preferential drainage of the left hepatic duct. We have reviewed a consecutive seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 0 publications
1
67
0
2
Order By: Relevance
“…On the other hand, an increased risk of cholangitis has been described if only one side is drained [1, 12,13]. Moreover, bilateral drainage is more physiologic than unilateral drainage [1, 12,14,15]. We perform unilateral SEMS placement in principle, but bilateral SEMS placement is necessary in cases with prolonged jaundice or contralateral cholangitis after unilateral drainage.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, an increased risk of cholangitis has been described if only one side is drained [1, 12,13]. Moreover, bilateral drainage is more physiologic than unilateral drainage [1, 12,14,15]. We perform unilateral SEMS placement in principle, but bilateral SEMS placement is necessary in cases with prolonged jaundice or contralateral cholangitis after unilateral drainage.…”
Section: Discussionmentioning
confidence: 99%
“…Decompression of both left and right hepatic ducts ideally requires the insertion of two stents, although there is evidence that unilateral stent insertion can be attempted, with good palliation [5], particularly if MRCP is utilized to direct stent placement [6]. Despite anatomical considerations suggesting that the left hepatic duct should be preferentially stented, it has been previously shown that drainage of the most technically accessible system will achieve adequate palliation in over 80% of patients [7].…”
Section: Hilar Versus Distal Strictures Of the Common Bile Ductmentioning
confidence: 99%
“…However, they did translate into significantly more re-interventions (p = 0.05) and longer total hospital stay (p = 0.03), as well as costs among patients treated with plastic compared to metal stents. In a retrospective study by Polydorou et al [31, 52], comprising 151 patients and comparing endoscopic drainage of the right versus the left hepatic lobe, no significant differences were found regarding procedure-related morbidity and survival. Unilateral hepatic drainage at the first attempt has been found to afford good palliation in 80% of patients in another study by Polydorou et al [32], and by Freeman et al [55] who registered no post-procedure cholangitis episodes.…”
Section: Resultsmentioning
confidence: 99%
“…Such measures will hopefully prevent septic complications from translating into increased mortality and reduced survival [32, 55]. Although based on one RCT only [4], and there are few other data to support this view (table 4), the findings suggest that the ductal system (right or left hepatic duct according to Polydorou et al [31, 52]), easily filled with contrast medium and most easily/immediately accessible by guide wires, should be negotiated and subsequently drained with large-bore plastic or metal stents. This mode of action would also be appropriate with regard to survival and desired improvement in QOL [32].…”
Section: Discussionmentioning
confidence: 99%